Szenci Molnár Religio-emblémájának forrásai, változatai - Imre, Mihály (Studia Litteraria, 2026)
The engraved print known as Igaz Vallás (True Religion), featuring a poem translated by Albert Szenci Molnár and an engraving by Dominicus Custos was published in Augsburg in 1606. This work is a variant of the 1576 Amsterdam print, which featured Beza’s poem translated into several different languages. The Dutch engraving was a portrayal of a protest against Spanish oppression. By 1606, Beza’s poem had a tradition that dated back for several decades. The prints published in Amsterdam and later in Augsburg placed the allegorical female figure into specific historical and social circumstances, meanwhile the old versions had been of allegorical nature with the female figure engaging in discussion with the readers of the poem. The first versions pictured a female figure leaning on a cross, crushing death under her feet. From 1560 onwards, the allegorical engraving, a picture and poem together, was commonly used without a title and with titles, in protestant publications, confessions, psalms and in Bible editions; furthermore, it was used by German, French, Swiss and English printers as typographic insignia. The front cover of Szenci Molnár’s translation of Calvin’s work (Institutio Religionis Christianae, 1624) displayed a version of the picture significantly different from the ones before. It displayed only the allegorical female figure, and the translation of Beza’s poem was placed before Calvin’s text. Beza’s poem appeared in Latin in the anthology by Georgius Carolides, Szenci Molnár’s patron in Prague. Péter Beregszászi Tóth’s collection of poems included the Hungarian adaptation of the old poem of complaints as a lament against protestant religious grievances of the seventeeth and eightteenth centuries.